Spatially Adaptive Column Fixed-Pattern Noise Correction in Infrared Imaging System Using 1D Horizontal Differential Statistics - Yanpeng Cao; Zewei He; Jiangxin Yang; Yanlong Cao; Michael Ying Yang (IEEE Photonics Journal)
In this paper we present a novel non-uniformity correction (NUC) method to remove column fixed-pattern noise (FPN), which is introduced by non-uniformity of on-chip column-parallel readout circuit in uncooled infrared focal plane array. We first define a new image statistic measurement, which is named as 1D horizontal differential statistics, to differentiate column FPN from structural edges, and further propose a filtering scheme to adaptively compute noise terms in structure and non-structure regions by applying different correction models. The proposed NUC technique combines the advantages of global- and local-based correction methods, thus can effectively eliminate column FPN without losing original thermal details. The performance of the proposed method is systematically evaluated, and is compared with the state-of-the-art column FPN correction solutions using realistic infrared images.